Tourist Experiences in Creative Cultural Attractions: A Demographic Perspective - Anwar Alawi; Adila Sosianika; Lina Setiawati (Journal of Marketing Innovation (JMI), 2022)
Creative tourism is one of the sectors that is predicted to grow significantly in the future. Saung Angklung Udjo (SAU) is a creative cultural attraction that presents various Sundanese cultural performances typical of West Java, Indonesia. This study aims to determine the differences in tourist experiences with cultural attractions from SAU based on demographic factors. The self-administered questionnaires were distributed directly to tourists who had watched Sundanese cultural performances at SAU. The data collected within a period of 31 days were 419 respondents. This number consists of domestic and international tourists. The data obtained in this study were processed using descriptive analysis, ANOVA, and T-test to examine the difference of perception between the tourists. The results reveal that there is a difference of perception among tourists based on tourist education on escape, peace of mind, involvement, and interactivity dimension. Moreover, there are differences in perceptions between tourists based on the origin of the region. The results of this study give input for creative tourism industry companies in making marketing strategies based on an understanding of the tourist experience with the creative cultural attractions.